2012
DOI: 10.2131/jts.37.1083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoke exposure on the expression of cardiac hypertrophic genes, cytochrome P450 enzymes, and oxidative stress markers in rats

Abstract: -Various experimental and clinical studies strongly support a cigarette smoke-heart disease association and suggest possible mechanisms, unfortunately, the involvement of genetic modulations remain unexplored. Thus, the main aim of the current study was to evaluate the effects of sub-chronic cigarette smoke exposure on the mRNA expression of cardiac hypertrophy genes, cytochrome P450 (CYP) enzymes, and the oxidative stress markers in heart rats. For this purpose, Wistar albino rats were exposed to increasing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…This also correlates well with the presence of BaP in the studied incense types. Consistent with our findings, previous studies have described a positive correlation between induction of CYPs and oxidative stress in response to environmental toxicants (Al-Arifi et al, 2012;An et al, 2011;Gentner & Weber, 2012;Raza et al, 2013;Tsuji et al, 2011). Importantly these toxicants like incense smoke, have considerable amounts of BaP as an active agent.…”
Section: Discussionsupporting
confidence: 93%
“…This also correlates well with the presence of BaP in the studied incense types. Consistent with our findings, previous studies have described a positive correlation between induction of CYPs and oxidative stress in response to environmental toxicants (Al-Arifi et al, 2012;An et al, 2011;Gentner & Weber, 2012;Raza et al, 2013;Tsuji et al, 2011). Importantly these toxicants like incense smoke, have considerable amounts of BaP as an active agent.…”
Section: Discussionsupporting
confidence: 93%
“…Al-Arifa et al demonstrated that exposing rats to ETS resulted in increased mRNA expression of oxidative stress genes as well as significant increases in a number of markers of oxidative stress (heme oxygenase 1, catalase, cyclooxygenase and glutathione S-transferase) [21]. Raji et al showed that exposure of rat aortic rings to cigarette smoke impaired nitric oxide-mediated endothelial function via increased generation of superoxide anion [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke contains over 4,000 chemicals, 70 of which are known toxins or carcinogens . Smoking is strongly associated with cardiovascular , pulmonary , and immune diseases, and also with cancer , birth defects , and impaired wound healing .…”
Section: Introductionmentioning
confidence: 99%